(3JGQjN eOjfI GUHgGfs - (3CMeO Hf YHO Gddg Hf CMeO GdCUHgGfj, CHh fYje, J (B430 (3g` s ((3jhSa Hf Ndjd Hf YHO Gddg GdOeTbi s)
(3ChdgG (B:s
(3CNHQfG jhSa Hf Ndjd Hf YHO Gddg GdOeTbi bQGAI YGdjg bGd GdTjN CeG HYO aEf HYV GdCNhGf ai fXe cJGH eTJed Ydi CSGei GdQhGg hGdeMOKjf ef Cgd HdOfG GUHgGf s
(3BNQgG (B:s
(3djdi HfJ CMeO Hf eSde Hf TYjH GdhdGOi GdeOjKi BNQ GdcJGH s
(3QhGjI CHj Ydi GdMSf Hf GdMOGO GdebQi hYdjg SeGYGJs
(3hfbhdGJs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI eJhSWI s
Keywords: (3eJaQbGJs